(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this in-vitro study was to evaluate the effect of eugenol-containing temporary fillings on shear bond strength of composite to dentin and determine the efficiency of dual bonding technique in improving the bond strength using Adper Single Bond 2 adhesive with 3M composite. Thirty sound human upper first premolars were used in this study. The occlusal surface of each tooth was ground to expose superficial dentin layer, and then dentin bonding agent was directly applied onto freshly prepared dentin together with cylinder of 3M composite and light cured (group I, control group). Dentin surface pre-treated with zinc oxide eugenol temporary filling, then dentin bonding agent together with a cylinder of 3M composite (group II, single bonding technique). While in group III dentin bonding agent was applied first on the dentin surface and light cured, then zinc oxide eugenol temporary filling was added for one week, after removal of temporary filling dentin bonding agent together with 3M composite was applied and light cured (dual bonding technique). The shear bond strength of all the specimens was determined using Zwick universal testing machine. The results showed that all temporary filling treated groups (II and III) had lower mean shear bond strength compared to control group (group I), whereas compared to single bonding technique, dual bonding technique significantly increased the shear bond strength.